An Investigation of Health Status Indicators: An Analytics Approach to Community Health in the United States - Balan, Shilpa; Sunnam, Kanishka; Khan, Aysha (Journal of Strategic Innovation and Sustainability, 2019)
It is vital to improve individual outcomes for overall community health; therefore, this study reviewed some of the major components of community health status indicators—heart disease, lung cancer, and breast cancer—from 1994 to 2003 in the United States. Using Tableau analytics software, we analyzed an open data set made available by the Centers for Disease Control and Prevention to extract insights and represent the findings visually. Our analysis revealed that the most deaths in the United States were due to heart diseases. From 1994–2003, Kentucky had the highest number of deaths due to lung cancer and Ohio had the highest number of deaths due to breast cancer. The current findings can be used to advance community health policy strategies to deliver better healthcare models and improve public health.